Bridging the gap between defossilization and decarbonization to achieve net-zero industry - Steven Griffiths; Benjamin Sovacool; Marfuga Iskandarova; Hans Jakob Walnum (Environmental Research Letters)
This paper examines the compatibility of broad decarbonization efforts, as embodied in the circular carbon economy (CCE) framework, with a narrower concept of defossilization in achieving net-zero industry. Through case studies of the United States, Norway, and the United Arab Emirates (UAE), we analyze national industrial decarbonization strategies and present findings from extensive fieldwork, including 139 expert interviews and 124 site visits supplemented with document analysis. Our results reveal that CCE and defossilization, which is defined as decarbonization through the elimination of fossil fuel extraction and use, are potentially compatible concepts in the long-term pursuit of net-zero industry. The CCE approach, which incorporates energy efficiency, renewable energy, electrification, low-carbon fuels, and carbon capture, utilization and storage, particularly offers a practical pathway for oil and gas (O&G) producing countries to transition towards net-zero industrial emissions. CCE allows these and similar countries to balance environmental goals with technical, economic, social and political challenges associated with defossilization. The case studies demonstrate that all three countries are adopting CCE strategies tailored to their unique contexts. The US emphasizes a portfolio approach integrating multiple technologies, the UAE focuses on leveraging existing fossil fuel infrastructure for CCE efforts, and Norway capitalizes on its abundant renewable resources while investing in carbon capture and storage and hydrogen projects utilizing its extensive O&G sector expertise and resources. Key policy recommendations include technology and policy leadership from countries pursuing a CCE framework, encouragement of public–private partnerships in the deployment of CCE technologies and ensuring social equity as net-zero industry is pursued in the near and long term. We also summarize existing approaches, pathways, and frameworks for industrial decarbonization, as well as barriers and challenges. We lastly call for further research on integration of CCE and defossilization visions, strategies and roadmaps and a strong focus on international cooperation in achieving net-zero industry.